Indonesian Law and Artificial Intelligence: Balancing Accountability, Ethics, and Innovation - Rangga Hotman Hasibuan; Aurelya Jessica Rawung; Fidel Jeremy Wowiling (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
Artificial intelligence (AI), which includes computing for perception, cognition, and action, raises complicated legal issues. This research investigates AI's influence and legal implications, focusing on its autonomy in communication and creativity, which raises problems about language, intellectual property, and ethical accountability. Discussions differ depending on whether they are influenced by the Common Law or Civil Law systems. While Common Law defines AI as